2022
DOI: 10.3390/foods11030249
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on Poultry Meat from Antibiotic Free and Conventional Farms: Can Metagenomics Detect Any Difference?

Abstract: Antibiotic free farms are increasing in the poultry sector in order to address new EU regulations and consumer concerns. In this pilot study, we investigated whether the efforts of raising chickens without the use antibiotics make any difference in the microbiome of poultry meat eaten by consumers. To this aim we compared the microbiomes characterizing caeca and the corresponding carcasses of two groups of chickens reared, one reared on a conventional farm and one on an antibiotic-free intensive farm. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
2
19
1
Order By: Relevance
“…More recently, a single antibiotic-free broiler farm, located in northern Italy, was investigated to quantify some representative ARGs at different sampling sites [ 15 ]. Finally, a metagenomic approach, with the aim to analyze the cecal resistome of broiler carcasses at the slaughterhouse, was performed by De Cesare et al [ 14 ]. In this respect, our study represents a first attempt to compare the distribution of different ARGs against several classes of antibiotics between conventional and antibiotic-free poultry farming systems in Italy, sampling the fecal specimens at the flock level and applying a rapid, low-cost, and relatively easy-to-perform method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a single antibiotic-free broiler farm, located in northern Italy, was investigated to quantify some representative ARGs at different sampling sites [ 15 ]. Finally, a metagenomic approach, with the aim to analyze the cecal resistome of broiler carcasses at the slaughterhouse, was performed by De Cesare et al [ 14 ]. In this respect, our study represents a first attempt to compare the distribution of different ARGs against several classes of antibiotics between conventional and antibiotic-free poultry farming systems in Italy, sampling the fecal specimens at the flock level and applying a rapid, low-cost, and relatively easy-to-perform method.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study, carried out to investigate the intestinal microbioma and ARGs from conventional and antibiotic-free chickens, highlighted a significantly lower antimicrobial resistance load in antibiotic-free production lines. However, this evidence disappeared when the corresponding carcasses were compared [ 14 ]. Conversely, Salerno et al [ 15 ] demonstrated that the abundance of ARGs harbored by the microbial community coming from broilers raised without antibiotics can be considered comparable to what has been reported in conventional farms.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the effects of different rearing management programs, including CONV and RWA, on growth performance and meat quality in broiler chickens have been investigated in both research and commercial settings [ 20 ]. Antibiotic effects on the gut microbiome composition and diversity have also been investigated in several research trials; however, whether the results of these studies reflect the changes in microbiome under field conditions remains to be investigated [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a higher evenness and diversity were observed in the cecal microbiome of chickens treated with a cocktail of antibiotics compared to the control group that did not receive any antibiotics or feed additives [ 22 ]. Diverse factors, such as gut health management practices and chicken age and breed, can influence the microbiota diversity and population [ 20 , 21 , 23 ]. The notable increase in the cecal microbiome richness and diversity in the conventionally grown chickens on days 10 and 24 could be due to the elimination of the growth of microorganisms in a broad sense by antibiotics might have resulted in an increased abundance of nutrients and ecological niches for the growth of endogenous and exogenous microbes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shotgun whole-metagenome sequencing (WMS) is a reliable tool that can provide a comprehensive and high-resolution analysis of the microbiome and resistome ( Schmieder and Edwards, 2011 ; Nesme et al, 2014 ; Ghanbari et al, 2019 ; Ma et al, 2021 ), and it has been applied to quantify the abundance of many resistance genes in parallel in poultry ( Wang et al, 2017 ; Kumar et al, 2020 ), cattle ( Thomas et al, 2017 ), pig ( Ghanbari et al, 2019 ; Mencía-Ares et al, 2020 ) and the human gut ( Feng et al, 2018 ). Other metagenomic studies have found multiple ARGs in chicken gut as well ( Tong et al, 2017 ; Xiong et al, 2018 ; Eckstrom and Barlow, 2019 ; Wang Y. et al, 2021 ; De Cesare et al, 2022 ). However, WMS provides only limited information regarding ARG activity or the overall functional profile of the active microbial community.…”
Section: Discussionmentioning
confidence: 93%